The importance of epistemological discussion in contemporary times and the contribution of Freire's critical pedagogy to education - Silva , Marcos Antonio da; Santos , Débora Cristine Fernandes Oliveira dos (Seven Editora, 2024)
This article explores the relevance of the epistemological discussion in contemporary times and the contribution of Freire's critical pedagogy to education, highlighting how reflection on the nature of knowledge is fundamental to understanding the challenges faced in an increasingly complex and interconnected society. We discuss the impact of epistemology in the areas of science, technology, education, and culture, highlighting its influence on the formation of paradigms and the search for answers to fundamental questions. Finally, the work brings reflections on the theoretical contributions of Paulo Freire's critical epistemology to the study of education and its relevance to social transformation. DOI:https://doi.org/10.56238/sevened2024.009-022